Analysis and Design of Light Vehicles for Rural Roads Considering Vibration and Its Performance - Manoj Kumar Singh, Bharat Raj Singh (International Journal of Intelligent Systems and Applications in Engineering, 2023)
This paper investigates light vehicle vibration due to rural road geometry. Normally due to bumps, potholes, uneven road conditions, the life of such vehicles are getting reduced. The mathematical model with higher degrees of freedom was developed and simulated on Matlab/Simulink software. Various independent/dependent parametric variables are considered such as: bumps, pitching, bounce, suspension, tire stiffness coefficient and damping etc. The simulation is performed over a range of bump heights (in the range of 0.025 m, 0.050 m, 0.075 m, 0.100 m). , 0.125 m and 0.150 m) and the vehicle speed is kept from 25 km/h to 125 km/h. Simulation results show that vehicle performance and comfort is achieved at higher speed of 65 km/h in the very poor rural road conditions in India. It is also observed that the vehicle ride can be improved by using proper tyre stiffness coefficient, suspension, damping devices and sprung mass and unsprung mass when designing a car model is done with seven degrees of freedom.